2017
DOI: 10.4172/2329-6771.1000193
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hepatotoxicity Induced by Doxorubicin

Abstract: Doxorubicin (DOX) has been used in the treatment of variety of cancers but its administration is limited by a dosedependent toxicity. Its cytotoxic effects on malignant cells have shown an increase in the risk of cardiotoxicity, hepatoxicity, renal insufisance.Antioxydants have been explored for both their cancer preventive properties and chemodulatory of DOX toxicity. Resveratrol (RSV) is a polyphenolic constituent of several dietary mainly of grapes and wine origin recently its anticancer potential has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 119 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…Hepatotoxicity: Evaluation of apoptotic cell death and ALT DXR induces oxidative stress and is characterized by accumulation of reactive oxygen species (ROS), which decrease antioxidant defence systems, resulting in oxidative damage of DNA and apoptotic cell death (Song et al, 2019). It has been shown that oxidative stress is a major contributor of DXR-induced hepatotoxicity (Bengaied et al, 2017;Rashid et al, 2013). Obesity is associated with low grade chronic in ammation, excessive ROS production and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatotoxicity: Evaluation of apoptotic cell death and ALT DXR induces oxidative stress and is characterized by accumulation of reactive oxygen species (ROS), which decrease antioxidant defence systems, resulting in oxidative damage of DNA and apoptotic cell death (Song et al, 2019). It has been shown that oxidative stress is a major contributor of DXR-induced hepatotoxicity (Bengaied et al, 2017;Rashid et al, 2013). Obesity is associated with low grade chronic in ammation, excessive ROS production and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DXR can induce hepatotoxicity, which limits its e cacy in anticancer therapy, resulting in poor patient prognosis and decreased overall survival of cancer patients (Bengaied et al, 2017;Song et al, 2019). DXR-induced oxidative stress is characterized by accumulation of reactive oxygen species (ROS), which decrease antioxidant defence systems, resulting in oxidative damage of deoxyribonucleic acid (DNA), therefore, mediating apoptotic cell death in hepatic tissue (Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, ROS attacks inorganic phosphates, thus depleting hepatocytes of ATP and consequently triggering apoptosis. These events permit the escape of cytosolic enzymes, for example, ALT, AST, and GGT, from hepatocytes into the circulation, thereby increasing their serum levels [1,2,7,20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DOX use increased the risk of developing liver injury, for example, acute/subacute liver necrosis, toxic hepatitis, and hepatic coma, by 1.29× across all types of cancer [5,6]. Metabolism of DOX in hepatocytes generates an abundance of free radicals, and the resulting oxidative stress induces DNA damage, lipid peroxidation, disturbance of membrane integrity, and ATP depletion, all of which culminate in apoptosis [1,7]. Currently, toxicity prevention only comprises dosage optimization and antioxidant supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…DXR can also be detrimental to other organs, such as the liver, which plays an important physiological role in metabolism, glycogen and triglyceride storage, plasma protein synthesis and detoxification of toxic metabolites [ 8 ]. It has been shown that DXR can induce hepatotoxicity, which limits its efficacy in anticancer therapy, resulting in poor patient prognosis and decreased overall survival of cancer patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%